ChemInform Abstract: Ferroelectricity Driven by Twisting of Silicate Tetrahedral Chains. Issue 43 (7th October 2013) - Taniguchi, Hiroki; et al., et al.
Abstract Single crystals of Bi2SiO5 are prepared from a mixture of Bi2O3 and SiO2 (Pt crucible, 1373 K, 2 h) and characterized by micro‐Raman scattering, powder XRD, and TEM.